The professional orientation to the masonry specialty: a system of activities - Jóse Andrés Gómez Torres; Jesús Torres Domínguez; Vadim Aguilar Hernández (Revista MENDIVE, 2018)
The specialty Masonry in Technical and Vocational Education is of great importance given the mission that has to train workers who have to use the most efficient and updated techniques and technologies for the construction of buildings and other construction works. In the pedagogical practice manifested a contradiction expressed in the need to raise the quality of the professional training of the workers in the specialty Masonry, however, there were inadequacies in the work of professional guidance with students who attend the first year in the Polytechnical center "Leonides Blanco", reflected in the insufficient inclination towards the study profile, which led to the failure of a percentage of students. The objective of the work was to elaborate a system of activities that perfected the process of professional orientation towards the specialty Albañilería the first year at the "Leonides Blanco" PolytechnicCenter. In the investigative process, the dialectical-materialist method was assumed as the general method, which supported the theoretical methods, the application of statistical techniques that made possible the study and systematization of the theoretical and methodological foundations of the process under investigation. The practical significance is expressed in a system of activities that contributed to the professional orientation of the first-year students of the specialty Masonry, which guarantees a relevant initial training process, depending on the demands of the professional model and the needs educational and social